2020
DOI: 10.3390/ani10122272
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Properties and Oxidative Indices of Broiler Breast Meat Affected by Wooden Breast Abnormality

Abstract: Wooden breast (WB) abnormality adversely impacts the quality of chicken meat and has been linked with oxidative stress. In this study, breast samples were taken from carcasses of 7-week-old Ross 308 broilers 20-min and 24-h postmortem. Five WB and seven non-WB control samples were assigned based on palpatory hardness (non-WB = no unusual characteristics and WB = focal or diffused hardness). WB exhibited lower contents of protein and the amino acids, i.e., isoleucine, leucine and valine, lighter surface color, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 80 publications
3
24
1
Order By: Relevance
“…Focusing on CB breeds, average values of moisture and fat content of the control CB were about 1.5 and 30% greater than those of their stressed counterparts. The results for CB breast were consistent with the characteristics of the breasts affected with growth-related myopathies ( Soglia et al, 2016 ; Cai et al, 2018 ; Malila et al, 2018 ; Dalle Zotte et al, 2020 ; Maharjan et al, 2020 ; Thanatsang et al, 2020 ).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Focusing on CB breeds, average values of moisture and fat content of the control CB were about 1.5 and 30% greater than those of their stressed counterparts. The results for CB breast were consistent with the characteristics of the breasts affected with growth-related myopathies ( Soglia et al, 2016 ; Cai et al, 2018 ; Malila et al, 2018 ; Dalle Zotte et al, 2020 ; Maharjan et al, 2020 ; Thanatsang et al, 2020 ).…”
Section: Resultssupporting
confidence: 81%
“…This could impair the muscle regeneration process and lead to muscle abnormalities, including emerging myopathies known as white striping (WS) and wooden breast (WB), among the chickens exposed to thermal challenge ( Aslam et al, 2021 ). Several studies indicated chemical changes, that is, reduced protein and increased fat content in chicken meat affected with those abnormalities ( Kuttappan et al, 2012 ; Petracci et al, 2014 ; Malila et al, 2018 ; Thanatsang et al, 2020 ). Overall, the incidence could not only affect economic returns of broilers but also potentially dilute nutritional properties of chicken breast meat, which is generally recognized as an inexpensive source of food protein in several regions.…”
Section: Introductionmentioning
confidence: 99%
“…in the FG might partly be induced by an intracellular Ca 2+ overload following muscle damage [66] consistently reported in breast muscles affected by WS and WB abnormality [12,67,68].…”
Section: Plos Onementioning
confidence: 88%
“…Today, the actual role of CAMKKβ in skeletal muscle is still under investigation. Up-regulated CAMKK2 in the FG might partly be induced by an intracellular Ca 2+ overload following muscle damage [ 66 ] consistently reported in breast muscles affected by WS and WB abnormality [ 12 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of CrPic + VC in the chicken diet led to an increase in the pH of breast meat compared to C group. pH is considered one of the crucial variables determining meat quality [41]. According to Berri et al [42] the normal pH values of chicken meat at 15 min postmortem are around 6.2 to 6.5, whereas normal ultimate pH values are around 5.8 [43].…”
Section: Discussionmentioning
confidence: 99%